Simple preparation method of biopolyester film bag material with high starch content, high strength and low cost
By increasing the starch content in the biopolyester film bag material and using amphiphilic triblock copolymer to increase capacity, combined with the low-temperature high-mixture and intensive extrusion process, the problem of insufficient strength of the existing biopolyester film bag is solved, and the preparation of high-strength and low-cost biopolyester film bag material is achieved.
Patent Information
- Application Number
- CN202411805756.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-28
AI Technical Summary
The existing biopolyester PBAT/PLA film bags are insufficient in strength and are easy to puncture, and calcium carbonate is added to reduce costs, the material density is heavy, brittle and easy to break, resulting in a short shelf life.
Using a high starch content biopolyester film bag material preparation method, the dried PBAT, PLLA, starch, amphiphilic triblock copolymer PPG, biochain extender and antioxidant are dried at low temperature and mixed at high speed, and then melt-refined and extruded in a intensive extruder to obtain high-strength biodegradable material.
It significantly improves the starch content, improves the strength and toughness of the biopolyester film bag, has a tensile strength of 15-26.8MPa, and a break elongation of 277%-421%. It also reduces production costs, and has simple process operation, easy material availability and good repeatability.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biodegradable polymer materials, and in particular relates to a simple preparation method of a high-starch content, high-strength, and low-cost biopolyester film bag material. Background Art
[0002] Biopolyesters such as PBAT and PLA have good biodegradability, and gradually replacing traditional plastic products with biomaterials is in line with the development trend of low-carbon and environmental protection. The processing performance of polybutylene adipate / terephthalate (PBAT) is similar to that of low-density polyethylene (LDPE). It has good ductility and can be processed into films, woven bags, dust-proof nets, etc., but its strength cannot meet certain application occasions; polylactic acid has the advantage of high strength, but it fractures brittlely, so PLA is usually added to the PBAT system to obtain mechanical characteristics with both strength and toughness. The price cost of biopolyesters PBAT and PLA is much higher than that of traditional petrochemical raw materials. Usually, 20% to 40% calcium carbonate and starch are added to them to reduce the production cost of biopolyester materials. However, materials such as film bags after adding calcium carbonate usually show high density, brittleness, easy to break, and thick bags. In recent years, thermoplastic starch has gradually been added to replace calcium carbonate. Starch is a type of degradable natural polymer material with the advantages of wide sources, low price, and easy biodegradation. However, hydrophilic starch has poor interfacial compatibility with biopolyester PBAT / PLA matrix, low interfacial adhesion between the component phases, and easy yellowing and degradation of starch during thermoplastic processing. As a result, the existing commercially available biopolyester PBAT / PLA film bags have the disadvantages of weak strength, easy puncture, mechanical strength less than 10MPa, and short shelf life. Therefore, it is necessary to develop new technologies to achieve compatibility between starch and PBAT / PLA matrix, increase starch content, and at the same time improve the strength of biopolyester PBAT / PLA film bags and control costs. Those skilled in the art are in urgent need of developing a simple preparation method for high-starch content, high-strength, low-cost biopolyester film bag materials to meet existing usage requirements and market demands. Summary of the invention
[0003] The purpose of the present invention is to provide a simple preparation method of a bio-polyester film bag material with high starch content, high strength and low cost, so as to solve the above technical problems.
[0004] A simple preparation method of a high-starch content, high-strength, low-cost biopolyester film bag material comprises the following steps: (1) drying 47-52 parts of PBAT, 7.5 parts of high molecular weight polylactic acid PLLA, 25-45 parts of starch, 5-10 parts of amphiphilic triblock copolymer PPG, 0-2 parts of biochain extender and 1 part of antioxidant at low temperature for 6 hours, and mixing at high speed in a cooling and temperature-controlled mixer to obtain a pre-dispersed mixture; (2) The pre-dispersed mixture is added to a counter-rotating twin-screw extruder with integrated mixing and extrusion. The mixture is first melt-mixed and reacted in situ before extrusion is started. The extrudate is cooled and cut, and the pellets are collected to obtain a high-strength biodegradable material. The material can be used in film bags, dust-proof nets, plastic parts, etc.
[0005] Furthermore, the main polymer component PBAT in step (1) is a copolymer of butylene adipate and butylene terephthalate; the high molecular weight polylactic acid has a number average molecular weight of 80,000 and a DPI of 1.2.
[0006] Furthermore, the amphiphilic copolymer PPG in step (1) is a triblock copolymer of polypropylene glycol-polyethylene glycol-polypropylene glycol.
[0007] Furthermore, the biological chain extender in step (1) is dicyclohexylmethane diisocyanate (HMDI) or epoxy chain extender YMX-3510P.
[0008] Antioxidant 3114, chemical name: 1,3,5-tris(3,5-di-tert-butyl-4-hydroxybenzene)-s-triazine-2,4,6-(1H, 3H, 5H)trione, CAS number is 27676-62-6.
[0009] Furthermore, the antioxidant in step (2) is antioxidant 3114.
[0010] Furthermore, the high-speed mixer in step (2) is equipped with a cooling temperature control system to maintain the system under high-speed cooling at 50-60° C. and a rotation speed of 600 rpm-800 rpm for 8-12 minutes, so as to achieve uniform mixing and dispersion of the mixture without softening, bonding or local reaction, and maintain the state of granular material.
[0011] Furthermore, in step (2), the temperatures from the feeding section to the die of the counter-rotating twin-screw extruder with integrated mixing and extrusion functions are 150° C., 165° C., 165° C., 165° C., 165° C., and 160° C., respectively.
[0012] Furthermore, in the step (2), the mixing function of the reverse twin-screw extruder has a length-to-diameter ratio of 42, and the pre-dispersed mixture is first melted and mixed for 4 to 10 minutes to react in situ, and then the extrusion valve is opened, cooled and pelletized to obtain a high-starch content, high-strength, low-cost biopolyester film bag material. The tensile strength of the blown film bag material is 15 to 26.8 MPa, and the elongation at break is 277% to 421%.
[0013] The present invention has the following beneficial effects: (1) Compared with the traditional chemical modification and compatibilization method, the present invention uses an amphiphilic triblock copolymer as PEG-b-PPG-b-PEG for compatibilization. The hydrophilic segment PEG has good compatibility with starch, and the hydrophobic segment PPG has good compatibility with PBAT and PLA. The interfacial adhesion is improved, which solves the problem of poor compatibility of multiphase interfaces. The amount of starch added is greatly increased to 45%, which significantly reduces the production cost. In addition, the processing method is simple to operate, the materials are easily available, and the repeatability is good.
[0014] (2) The present invention adopts a process improvement of low-temperature high-mixing and internal kneading extrusion to achieve low-temperature mixing to prevent local reaction and softening agglomeration affecting overall uniformity; a kneading module is added to the extrusion stage to achieve better reaction and mixing uniformity than traditional twin-screw extrusion, and then air cooling is used for shaping to avoid the drying and brittleness problems caused by traditional water cooling and oil cooling. Through these process improvements, simple and easily available materials can also obtain high performance, and finally realize the preparation of low-cost and easily repeatable bio-polyester film bag materials with high starch addition and low PLA addition. DETAILED DESCRIPTION
[0015] The present invention is described below with specific examples, but is not intended to be limiting of the present invention. Example 1
[0016] Raw materials: PLLA high molecular weight polylactic acid with a number average molecular weight of 80,000, DPI = 1.2, PBAT: JSC-210-X-LP; Suqian Liansheng antioxidant 3114. Xiaoxian Golden Corn Company's premium corn starch.
[0017] A simple method for preparing a high-starch content, high-strength, low-cost bio-polyester film bag material is as follows: (1) preparing a pre-dispersed mixture Weigh 62kg PBAT, 7.5kg polylactic acid, 25kg corn starch, 2.5kg PPG, and 1kg antioxidant 3114, dry at 45°C for 6h, put into a high-speed mixer and mix at 600rpm for 12min at a low temperature of 50°C to obtain a premixed granular material; (2) Preparation of modified membrane bag materials The pre-dispersed mixture prepared in step 1 is added to the twin-screw extruder, and the temperature from the feeding section to the die head is 150°C, 165°C, 165°C, 165°C, 165°C, 160°C. First, it is mixed for 4 minutes to melt and mix the materials in the pre-dispersed mixture and complete the in-situ reaction. Then, it is extruded, air-cooled, and granulated to obtain a high-starch content, high-strength, low-cost bio-polyester film bag material. The length-to-diameter ratio of the reverse twin-screw extruder with mixing function is 42. The pre-dispersed mixture is first melted and mixed in it to make it react in situ, and then the extrusion valve is opened, cooled and granulated.
[0018] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 1 has a tensile strength of 15.5 MPa and an elongation at break of 245%. Example 2
[0019] The difference between this embodiment and embodiment 1 is that the mass of PPG is adjusted to 5 kg, the other components are the same as those in embodiment 1, and steps (1) and (2) are the same as those in embodiment 1.
[0020] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 2 has a tensile strength of 18.9 MPa and an elongation at break of 432%. Example 3
[0021] The difference between this embodiment and embodiment 1 is that the mass of PPG is adjusted to 7.5 kg, the other components are the same as those in embodiment 1, and steps (1) and (2) are the same as steps (1) and (2) in embodiment 1.
[0022] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 3 has a tensile strength of 19.13 MPa and an elongation at break of 491%. Example 4
[0023] The difference between this embodiment and embodiment 1 is that the mass of PPG is adjusted to 10 kg, and the other components are the same as those in embodiment 1. Step (1) and step (2) of this embodiment are the same as steps (1) and step (2) of embodiment 1.
[0024] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 4 has a tensile strength of 16.1 MPa and an elongation at break of 505%.
[0025] By comparing the tensile strength and elongation at break results of the modified film bag materials prepared in Examples 1, 2, 3, and 4, it can be seen that the addition of the amphiphilic block PPG of the present invention can improve the compatibility between starch and the resin substrate, and the composite system prepared in Example 3 with a PPG content of 7.5% has the best uniformity and the best comprehensive mechanical properties. Example 5
[0026] The component formula of this embodiment is different from that of Example 3 in that the mass of corn starch is increased to 30 kg and the mass of PBAT is 57 kg; the operation steps of this embodiment are the same as those of Example 1.
[0027] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 5 has a tensile strength of 16.7 MPa and an elongation at break of 422%. Example 6
[0028] The difference between the component formula of this embodiment and that of embodiment 3 is that the mass of corn starch is increased to 35 kg and the mass fraction of PBAT is 52 kg. The operation steps of this embodiment are the same as those of embodiment 1.
[0029] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 6 has a tensile strength of 15.4 MPa and an elongation at break of 380%. Example 7
[0030] The difference between the component formula of this embodiment and that of embodiment 3 is that the mass fraction of corn starch is increased to 40 kg, and the mass of PBAT is 47 kg. The operation steps of this embodiment are the same as those of embodiment 1.
[0031] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 7 has a tensile strength of 13.2 MPa and an elongation at break of 286%.
[0032] By comparing the tensile strength and elongation at break of the high-starch content, high-strength, low-cost biopolyester film bag materials prepared in Examples 3, 5, 6, and 7, it can be seen that when the PPG mass fraction is fixed, good mechanical properties can be obtained when the starch content is between 25% and 40%, and the tensile strength is between 14.5 and 19.1 MPa, which can meet the mechanical property requirements of film bag nets and other applications. Example 8
[0033] Raw materials: PLLA high molecular weight polylactic acid with a number average molecular weight of 80,000, DPI = 1.2, PBAT: JSC-210-X-LP; Suqian Liansheng antioxidant 3114. Xiaoxian Golden Corn Company's premium corn starch.
[0034] A simple preparation method for a high-starch content, high-strength, low-cost bio-polyester film bag material is as follows: (1) Preparation of pre-dispersed mixed material: weigh 62 kg PBAT, 7.5 kg PLA, 25 kg corn starch, 5 kg PPG, 1 kg antioxidant 3114 and 0.7 kg YMX-3510P, dry at 45 ° C for 6 h; put into a high-speed mixer and mix at 800 rpm for 8 min at a low temperature of 50 ° C to obtain a pre-mixed granular material; (2) Preparation of modified membrane bag materials The pre-dispersed mixture prepared in step 1 is added into a twin-screw extruder, and the temperatures from the feeding section to the die head are 150°C, 165°C, 165°C, 165°C, 165°C, and 160°C. It is first mixed for 10 minutes to allow the materials in the pre-dispersed mixture to melt and mix and complete the in-situ reaction. It is then extruded, air-cooled, and granulated to obtain a high-starch content, high-strength, and low-cost bio-polyester film bag material.
[0035] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 8 has a tensile strength of 15.0 MPa and an elongation at break of 433%. Example 9
[0036] The difference between this embodiment and embodiment 8 is that the mass of the chain extender YMX-3510P is adjusted to 1.5 kg.
[0037] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 9 has a tensile strength of 16.2 MPa and an elongation at break of 286%. Example 10
[0038] The difference between this embodiment and embodiment 8 is that the weight fraction of the chain extender YMX-3510P is increased to 2 kg.
[0039] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 10 has a tensile strength of 17.4 MPa and an elongation at break of 231%. Embodiment 11
[0040] The difference between this embodiment and embodiment 8 is that the chain extender YMX-3510P is replaced with a chain extender 0.7 kg HMDI (Wanhua dicyclohexylmethane diisocyanate H1210).
[0041] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 11 has a tensile strength of 17.2 MPa and an elongation at break of 477%. Example 12
[0042] The difference between this embodiment and embodiment 8 is that the chain extender YMX-3510P is replaced by a chain extender 1.5 kg HMDI.
[0043] The high-starch content, high-strength, low-cost biopolyester film bag material prepared in Example 12 has a tensile strength of 22.1 MPa and an elongation at break of 356%.
[0044] By comparing Example 8, Example 9, and Example 10, it can be seen that when the content of the chain extender YMX-3510P increases from 0.7 to 1.5 and 2, the mechanical strength of the composite material gradually increases and the elongation at break gradually decreases. Taking into account the comprehensive performance of strength and toughness, the preferred YMX-3510P content is 1.5%; further comparing it with Examples 11 and 12, it can be found that the use of the chain extender as the HMDI system produces better mechanical strength, which may be due to the fact that HMDI can induce a faster reaction speed and obtain more cross-linking sites. The mechanical strength of the composite material with a high starch content can reach 22.1 MPa and the elongation at break is 356%, showing strong and tough characteristics.
[0045] Note: The tensile test was carried out on a CMT6104 microcomputer-controlled electronic universal testing machine (Shenzhen Xinsansi Co., Ltd.) according to GB / T.1040.2-2006 standard, with a sample size of 150 mm × 20 mm × 4 mm, a test speed of 50 mm / min, and a temperature of 25 °C.
[0046] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A simple preparation method of a high-starch content, high-strength, low-cost bio-polyester film bag material, characterized in that: The following steps are involved: (1) By weight, 47-62 parts of dried PBAT, 7.5 parts of high molecular weight polylactic acid, 25-45 parts of starch, 5-10 parts of amphiphilic triblock copolymer PPG, 0-2 parts of bio-chain extender and 1 part of antioxidant are placed in a cooling and temperature-controlled mixer for high-speed mixing to obtain a pre-dispersed mixture; (2) The pre-dispersed mixture is added to a counter-rotating twin-screw extruder with internal mixing and extrusion. The mixture is first melt-mixed and reacted in situ before extrusion is started. The extrudate is cooled and then cut and pelletized to obtain a bio-polyester film bag material with high starch content, high strength and low cost.
2. The simple preparation method of the high-starch content, high-strength, low-cost biopolyester film bag material according to claim 1 is characterized in that: The PBAT in step (1) is a copolymer of butylene adipate and butylene terephthalate; the high molecular weight polylactic acid has a number average molecular weight of 80,000 and a polymerization degree dispersion coefficient DPI of 1.
2.
3. The simple preparation method of the high-starch content, high-strength, low-cost biopolyester film bag material according to claim 1, characterized in that: The amphiphilic copolymer PPG in step (1) is a triblock copolymer of polypropylene glycol-polyethylene glycol-polypropylene glycol.
4. The simple preparation method of the high-starch content, high-strength, low-cost biopolyester film bag material according to claim 1, characterized in that: The biological chain extender in step (1) is dicyclohexylmethane diisocyanate or epoxy chain extender YMX-3510P.
5. The simple preparation method of the high-starch content, high-strength, low-cost biopolyester film bag material according to claim 1, characterized in that: The antioxidant in step (1) is antioxidant 3114.
6. The simple preparation method of the high-starch content, high-strength, low-cost biopolyester film bag material according to claim 1, characterized in that: The mixer in step (1) is equipped with a cooling temperature control system to maintain the system under high-speed cooling at 50-60° C. and 600-800 rotation speed for 8-12 minutes.
7. The simple preparation method of the high-starch content, high-strength, low-cost biopolyester film bag material according to claim 1, characterized in that: In step (2), the temperatures of the counter-rotating twin-screw extruder with integrated mixing and extrusion function from the feeding section to the die head are 150° C., 165° C., 165° C., 165° C., 165° C., and 160° C., respectively.
8. The simple preparation method of a high-starch content, high-strength, low-cost biopolyester film bag material according to claim 1, characterized in that: The length-to-diameter ratio of the reverse twin-screw extruder for internal mixing in step (2) is 42. The pre-dispersed mixture is first melted and internally mixed for 4 to 10 minutes to allow it to react in situ, and then the extrusion valve is opened and the mixture is cooled and pelletized.
Citation Information
Patent Citations
Method for improving PLA and PBAT compatibility
CN105368013A
Method for preparing biodegradable polylactic acid based composite material with high strength and high toughness by crosslinking reaction in extrusion process
CN107083032A
Starch-filled PLA / PBAT full-biodegradable composite material and preparation method thereof
CN110845830A
Biodegradable polylactic acid plastic bag and preparation method thereof
CN112210195A
Biodegradable composite modified film bag particle material and preparation method thereof
CN113773559A
Cited By
Hemp tree powder bio-based degradable material and preparation method thereof
CN120829627A